Plan de negocio para la empresa Globos Colombia, prestadora del servicio de vuelo en globo aerostático ubicada en el departamento del Quindío (2013)
In this research project, which is developed in tourism sector, mainly on adventure and contemplative tourism, we sought to obtain solid foundations to draw up a business plan for Globos Colombia enterprise, which provides the service of hot air balloon rides on the modalities of captive or free flight, and its market segment is comprised by men, women and children over 7 years old with a middle – high socioeconomic status. The realization of this business plan had as main objective the development of an efficient business model in order to strengthen and position this enterprise in the field of tourism services in Department of Quindío. Furthermore, through a market research, a technical and engineer analysis, a design of an organizational structure, a social and environmental study and a financial and economic analysis we sought to achieve a sustainable development for Globos Colombia enterprise, creating benefits not only for the owners, employees, suppliers, clients but also contributing to the improvement of Quindío’s tourism, considering that in this sector products and services will never be enough, therefore it is important to innovate and create new proposals constantly, especially it is necessary to focus these products into nature tourism, cultural tourism, adventure tourism, sun and beach tourism, meetings, congresses, events and incentives tourism, health and welfare tourism, which are part of departmental and national policies.